2015
DOI: 10.1371/journal.pone.0121548
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection in Chronically Inflamed Periapical Granulomas

Abstract: Periapical granulomas are lesions around the apex of a tooth caused by a polymicrobial infection. Treatment with antibacterial agents is normally performed to eliminate bacteria from root canals; however, loss of the supporting alveolar bone is typically observed, and tooth extraction is often selected if root canal treatment does not work well. Therefore, bacteria and other microorganisms could be involved in this disease. To understand the pathogenesis of periapical granulomas more precisely, we focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Additionally, a standard curve for EBV was also prepared using 1 × 10 6 DNA copies of EBV, as described previously (Makino et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, a standard curve for EBV was also prepared using 1 × 10 6 DNA copies of EBV, as described previously (Makino et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…The numbers of EBV DNA copies were determined using a standard curve, as described previously (Makino et al . ). The cell number of P. endodontalis was also determined using a standard curve.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Under “healthy” conditions, this indigenous microflora remains benign and assists the host by maintaining basal host immunity, thereby establishing symbiotic association. Influenced by various external and internal factors, however, this equilibrium may be disturbed leading to modulated immune responses (11). …”
Section: Introductionmentioning
confidence: 99%
“…Ferriera et al reported that 48% of apical abscesses samples had KSHV infections, whereas Chen et al detected HCMV in 29% of the patients with similar disease (12,13). A more recent study suggested that B cells and plasma cells in inflamed granulomas are a major source of EBV infection, and that EBV could play a pivotal role in controlling immune cell responses in periapical granulomas (11). The prevalence of herpesviruses varies across different reports, nonetheless, it is recognized that they may act as opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%